The effect of different roasting conditions on anthocyanin, total phenolic content, and antioxidant capacity of pomegranate peel / Nurin Adlina Mohd Zamrin, Siti Maisarah Abu Bakar and Muhammad Aidil Ibrahim - Mohd Zamrin, Nurin Adlina; Abu Bakar, Siti Maisarah; Ibrahim, Muhammad Aidil (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Pomegranate (Punica granatum L.) peel is a common agro-industrial waste, but high in phytochemicals such as hydrolyzable tannins, phenolics, flavonoids which includes anthocyanin, and other essential nutrients, making it a great natural source of antioxidants that may protect cells against oxidative damage caused by free radicals. Thus, it will be advantageous when the amount of extractable phenolic compounds yield can be increased by extracting using efficient extraction parameters. Therefore, this study aims to evaluate the impact of different roasting conditions which involve temperature (100°C, 150°C, 200°C) and duration (10 or 20 minutes) on the extractable anthocyanin, phenolic content, and antioxidant capacity of pomegranate peels. The phenolic compound extraction process was through the maceration method with 50% ethanol/H2O. The Folin-Ciaocalteu assay was applied to measure the phenolic content from extracts obtained while 2,2-diqphenyl-1-picrylhydrazyl (DPPH) assay was utilized to measure the antioxidant activity. The result showed that roasting at 100°C for 20 minutes yields the highest phenolic content of 4.404 mg GAE/g while at 150°C for 20 minutes, the highest anthocyanin content was recorded with a percentage of 1.33%. This was also correlated with the increase of the antioxidant capacity until the roasting temperature reached 150°C. The highest antioxidant activity with a value of 33.68% was detected at 100°C for 20 minutes. Overall, the roasting activity does have a significant impact in enhancing extractable phenolic compounds in pomegranate peel which thereby led to a significant increase in the antioxidant activity. Thus, this can provide more insights for future application of the roasting procedure on other fruit peel samples in phenolic compound extraction.